Effects of diet in improving iron status of women: what role for food-based interventions? - International Food Policy Research Institute (International Food Policy Research Institute, 2000)
This brief describes research in Bangladesh. The brief argues that poor diet quality and low bioavailability of dietary iron are important factors contributing to iron deficiency anemia (IDA). Nevertheless, can food-based interventions be successful in reducing IDA? Will such interventions be cost-effective as compared with alternative interventions such as supplementation? Unfortunately in attempting to answer these questions, little is known, under actual living conditions in rural areas, about the magnitude of the effects of various components of the diet in reducing IDA. Plant breeding holds great potential for providing a low-cost intervention that could help to improve iron status broadly for populations with a high prevalence of iron deficiency....Although cost-effective, plant breeding is only one of several interventions that are all required in tandem to reduce micronutrient malnutrition.